Peran Mahasiswa sebagai Representasi Generasi Muda dalam Aktualisasi Nilai Pancasila melalui Interaksi Sosial di Lingkungan Kampus (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study is motivated by the importance of actualizing Pancasila values in students’ lives, not only at the cognitive level but also in daily social interactions within the campus environment. Phenomena such as digital individualism, exclusivity in social relationships, and bullying practices indicate a gap between understanding and implementation of Pancasila values. This study aims to analyze the forms of Pancasila value actualization through students’ social interaction patterns and their implications for character building. The research employs a qualitative approach using a library research method, with secondary data derived from scientific journals, books, and relevant academic documents. Data collection was conducted through documentation study, while data analysis used descriptive-critical content analysis. The findings show that the actualization of Pancasila values is reflected in religious tolerance, rejection of bullying, cross-cultural inclusivity, deliberative decision-making, and fairness in academic collaboration. These results indicate that students’ social interaction serves as an important indicator of successful internalization of Pancasila values. Practically, this study highlights the importance of strengthening character education based on social practices to develop ethical, inclusive, and Pancasila-oriented young generations.